The novelty Mezilaurus conceicionensis (Lauraceae) and a key to the species of the genus from Brazilian Southeastern - Alves, Flávio Macedo; Burkowski Meyer, Pablo; Cézanne De Souza Assis, Leandro (Phytotaxa, 2022)
A new species, Mezilaurus conceicionensis (Lauraceae), from Southeastern Brazil, was discovered during fieldwork at Serra da Ferrugem, State of Minas Gerais. This new species is described and illustrated in this study, being distinguished from the remaining species of Mezilaurus species mostly by its globoid fruits. An identification key of the species of Mezilaurus from Southeastern Brazil is presented.